Institutional isomorphism and corporate social responsibility: towards a conceptual model - Roszkowska-Menkes, Maria; Aluchna, Maria (Journal of Positive Management, 2018)
Purpose: The paper proposes the conceptual framework for understanding the impact of corporate social responsibility (CSR) on companies viewed as the source of institutional pressure. According to the neo-institutional approach the response to institutional change leads to the organizational isomorphism, which means that companies adopt new rules and design and in result become similar following the same managerial practice. The adoption of new designs and practice represents the case of the diffusion and institutionalization of change in formal organization structure. Methodology/approach: The study is of theoretical character. It adopts the contribution proposed by the neo-institutional theory and CSR literature. Findings: The paper ties diffusion process of different CSR modes – defensive, charitable, promotional, strategic, systemic – and strategies with three isomorphism mechanisms - mimetic, coercive and normative. Further the study outlines future research opportunities. Practical implications: We argue that the most mature CSR practice represented by systemic mode is institutionalized from within organization through normative isomorphic pressures rather than as a result of coercive power or mimetic efforts.